Extraintestinal Clostridioides difficile Infection (CDI): A Recurrent Battle with Resilient Abdominal Wall Abscess - Justine Chinnappan; Murtaza Hussain; Dominic Awuah; Ekwevugbe Ogbon; Ghassan Bachuwa; Philip McDonald (European Journal of Case Reports in Internal Medicine, 2023)
Clostridioides (formerly Clostridium) difficile infection is a common and costly healthcare-associated infection. Extraintestinal C. difficile infection is rarely encountered, especially in isolation. We present a unique case of abdominal wall abscess presenting six months following gastrointestinal (GI) surgery. The patient was managed with computed tomography (CT) guided drainage of the abscess, placement of a drainage catheter, and aggressive broad-spectrum antibiotic treatment for a prolonged duration over multiple admissions.